Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.5047/eps.2011.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Rupture process and coseismic deformations of the 27 February 2010 Maule earthquake, Chile

Abstract: We estimated the spatial and temporal slip distribution for the 27 February 2010 Maule earthquake from teleseismic body wave data. To obtain a stable inversion solution, we used the data covariance matrix from the observation and modeling errors, incorporated smoothing constraints and determined their optimal values by using the Akaike Bayesian Information Criterion (ABIC). The fault rupture can be divided into three stages. For the first 30 s the rupture started as an elliptical crack elongated in the in-plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Some studies of the 2010 Maule earthquake support this hypothesis (Moreno et al, 2010;Pulido et al, 2011), even though the debate is still active as other studies indicate a limited overlap between seismic gap and coseismic slip (Lorito et al, 2011). A comparison of several source models for the Maule earthquake show, however, that there is a large uncertainty on the location of regions of large slip (i.e., Delouis et al, Figure 10.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies of the 2010 Maule earthquake support this hypothesis (Moreno et al, 2010;Pulido et al, 2011), even though the debate is still active as other studies indicate a limited overlap between seismic gap and coseismic slip (Lorito et al, 2011). A comparison of several source models for the Maule earthquake show, however, that there is a large uncertainty on the location of regions of large slip (i.e., Delouis et al, Figure 10.…”
Section: Discussionmentioning
confidence: 99%
“…(a) Average V S for the shallowest 10 m of soil (AV S10 ) in Lima . (b) Amplifications with respect to the engineering bedrock in Lima, defined as the average amplifications (0:05 ∼ 1 s) of the transfer functions at each grid point (V S ∼ 400 m=s) 2010; Lorito et al, 2011;Pulido et al, 2011;and Lay et al, 2010), so a definite conclusion based on this earthquake alone is difficult due to the uncertainties involved. On the other hand there are many other examples of coincidence between coseismic slip and interseismic coupling for worldwide subduction zones such as in Sumatra Konca et al, 2008), in Japan (Hashimoto et al, 2009;Loveless and Meade, 2011), and in Chile (Moreno et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coastal land-level changes were also reported by the field survey (FARIAS et al, 2010). Various source models of this earthquake have been proposed by using seismic waves (LAY et al, 2010;PULIDO et al, 2011), global positioning system (GPS) data (TONG et al, 2010), GPS and interferometric synthetic aperture radar (InSAR) data (DELOUIS et al, 2010;VIGNY et al, 2011), or geodetic data and tsunami waveforms (LORITO et al, 2011). Among them, VIGNY et al (2011) compiled the slip distributions from the aforementioned studies and compared them with the observed GPS data.…”
Section: Introductionmentioning
confidence: 99%
“…The dimensions of the fault plane were over 500 km length by 180 km width (LAY et al 2010;TONG et al 2010;POLLITZ et al 2011). Several authors studied the source of the earthquake using seismic waveforms (LAY et al 2010;PULIDO et al 2011), global positioning system measurements (MORENO et al 2010;TONG et al 2010), and tsunami data (WU and HO 2011;LORITO et al 2011;FUJII and SATAKE 2013). The field observations and tsunami records of these events indicate that the significant coastal impacts were locally concentrated.…”
Section: The Three Recent Chilean Tsunamismentioning
confidence: 99%